The Impact of Fiber Length on the Gain and Efficiency of Erbium Doped Amplifier - Razali, Naqiuddin; Awang, Noor Azura (Enhanced Knowledge in Sciences and Technology, 2025)
This study explores the potential of Bismuth-based Erbium-Doped Fiber Amplifiers (Bi-EDFAs) as a solution for high-capacity optical communication networks, particularly in dense Wavelength Division Multiplexing (WDM) systems. Bi-EDFAs, leveraging the unique optical properties of Bismuth-doped fibers, offer wideband amplification in the C+L band while addressing challenges like high erbium ion concentrations and self-saturation effects that affect gain uniformity and efficiency. By optimizing parameters such as pump power, fiber length, and doping levels, the research demonstrates the superior performance of Bi-EDFAs compared to traditional EDFAs. The findings position Bi-EDFAs as a promising technology for next-generation optical networks, with applications spanning backbone, metro, and access systems, while paving the way for further advancements in diverse optical environments.